Increase of insular exotic arthropod diversity is a fundamental dimension of the current biodiversity crisis - Borges, Paulo A. V. (2020)
A dramatic insect decline has been documented on the grasslands and forests of European or North American mainland. Yet, other parts of the world and other ecosystems remain much less studied with unknown patterns. Using a unique time-series dataset, we investigate recent trends on abundance and richness of arthropods sampled in Azorean native forest over 6 years (2013–2018). We test the hypothesis that biodiversity erosion drivers are changing the diversity and relative species abundance structure (species abundance distribution, SAD) of endemics, native non‐endemics and exotic species over time. We also examine temporal trends in abundance for each individual species. In contrast with mainland studies, we observed no decline in overall arthropod diversity, but a clear increase in the diversity of exotic arthropods and some evidence of a tendency for decreasing abundance for some endemic species. We also document stronger species turnover for exotic species, but no specific changes in the SAD. We argue that many changes, particularly in unique systems such as islands, will be noticed not at the richness but mostly at compositional level. Special attention should be given to exotic species which are known to be one of the major drivers of biodiversity erosion on islands.